Landscape Space: Integration of Culture and Nature - Sassan Seyedkalal; Shahram Pourdeihimi (مسکن و محیط روستا)
Landscape Space: Integration of Culture and Nature   Authors:     Dr. Shahram Pourdeihimi, MArch(SBU), PhD(Leeds)   Professor, school of architecture and Planning, Shahid Beheshti University     Sassan Seyedkalal, PhD Candidate(SBU), MArch(SBU), MLA(Guelph)     Keywords:   Landscape, landscape space, landscape and environment, binary thinking in landscape architecture, culture/nature     The word landscape encompasses a wide range of meanings varying from ideas and mental conceptions to land and physical environment surrounding human world. It is commonly attributed to place, environment, garden and scenery. Landscape as a concept is not equivalent to environment and it covers a broader realm than garden does. Landscape is a complex concept that embodies multiplicities of different intertwined meanings. It is surrounded with ambiguities and misconceptions, Therefore the concept of landscape needs clarification.   The spatial quality of Romantic gardens was the source of inspiration for development of the concept of space in architectural discourse. Landscape is a spatial concept and inherent spatiality of landscape architecture as one of the environmental design disciplines makes it a spatial discipline, yet rarely is the concept of space considered as the focus of study in theory of landscape architecture. Spatiality of landscape is the result of the interaction of culture and nature in specific places and over time. Landscape is conceived, perceived and through living it is experienced. Landscape space is bound into places with their geographical and topographical attributes.   Temporality is a fundamental characteristic of landscape that distinguishes it from buildings and architectural works, but seeing landscape as a timeless picture or scenery has pervaded discipline of landscape architecture since eighteenth century. Landscape is the outcome of interactions and interrelationships between natural processes, living beings and environment. Landscape is experienced in motion, change and growth. Space in landscape is experienced through time.   Landscape is the product of culture and it can be used as a medium for cultural expression and cultural change. Landscapes are representations of the quality of the relationship between man and his environment and dwelling therein.   The idea of landscape has been under influence of binary thinking and various binary sets such as self/other, culture/nature, ecological/artistic, picture/process and art/science have affected the way we relate to landscapes. These binaries have dominated theory and practice in various disciplines related to landscape. This study highlights the mediating role of landscape and landscape design as a cultural, natural and spatial medium bridging between two opposing poles of binary sets of concepts and meanings.   Today the environmental crisis in the world and emergence of sustainability as an environmental paradigm in academic and professional debates necessitates rethinking the relationship between culture and nature in landscapes: a reconciliation between aesthetic values and ecological values. Emergence of ecological aesthetics and ecological design is the outcome of a new vision toward relationship of man with nature.